Bank lending in an emerging economy: How does central bank reserve accumulation matter? - Van Dan Dang; Japan Huynh (Universitas Islam Indonesia, 2021)
Purpose - The paper examines the impacts of the central bank's foreign exchange reserves on bank lending, captured by the dimensions of quantity (loan growth) and quality (credit risk).Methods - This research analysis is based on bank-year observations in Vietnam during 2007–2019 and employs the two-step system Generalized Method of Moments in dynamic panels.Findings - This study finds that banks tend to increase their loan growth rate in response to reserves accumulation. Banks also expand loans and cash items on their asset structure while subsequently slashing total security investments and disaggregate government bond holdings. Our results also indicate that the central bank reserves accumulation is associated with less credit risk and more financial stability of the banking system.Implication - This paper supports the notion that reserve accumulation could be a complementary monetary policy tool for lending navigation and economic growth. Besides, reserve interventions may be used for financial stability, given the finding that it is found to curtail bank credit risk and financial instability.Originality - This paper contributes to the literature by focusing on critical aspects of bank lending, including quantity and quality, to paint a bigger picture of the benefits and costs of reserve accumulation and decompose bank asset portfolios into disaggregate components, thereby providing more insight into bank responses.